Social Capital and Collective Action in Rural Tourism: Lessons from Award-Winning Village Tourism in West Java - Rahmat Darmawan; Jenal Abidin; Revi Agustin Aisyanita (Journal of General Education and Humanities, 2026)
Background/Context: Community-based tourism (CBT) has become a central strategy in Indonesian rural development policy, yet despite substantial government investment, the overwhelming majority of registered tourism villages fail to achieve sustained competitiveness. Understanding what enables some villages to perform exceptionally remains a challenge for both scholars and practitioners. Research Gap / Problem Statement: Existing literature has extensively examined supply-side and infrastructural determinants of village tourism success, but has devoted far less attention to the internal social architecture of high-performing communities, specifically how social capital dimensions and collective action mechanisms interact to produce sustained tourism governance capacity in non-Western, rural contexts. Objective / Purpose: This study investigates how social capital and collective action mechanisms underpin the exceptional performance of Cisaat Tourism Village in Subang Regency, West Java, a nationally recognised winner of the Anugerah Desa Wisata Indonesia (ADWI) competition,  using Putnam’s (2000) tripartite social capital framework and Ostrom’s (1990) collective action theory. Methodology: An explanatory sequential mixed-methods design was employed. A structured survey was administered to 150 community members and analysed using PLS-SEM. Twelve in-depth interviews with key stakeholders were analysed through reflexive thematic analysis. Key Findings / Results: All three dimensions of social capital: bonding, bridging, and linking, all exert significant positive effects on collective action (p < 0.01), which in turn strongly predicts tourism village sustainability (p < 0.001, β = 0.58). Bridging social capital emerged as the strongest predictor of collective action (β = 0.43). Qualitatively, three enabling themes were identified: trust as a foundational resource, external networks as catalysts for collective mobilisation, and shared vision sustained through inclusive leadership. Conclusion: Gotong royong, the indigenous Indonesian practice of mutual cooperation, functions as a culturally specific mechanism for bonding social capital that extends Ostrom’s collective action framework to non-Western contexts. Implications / Contribution: These findings offer a replicable, evidence-based model for village tourism development policy in Indonesia and across the Global South, and provide a validated Social Capital Scale for integration into national tourism village accreditation systems.